Student Preception Toward Chatgpt In Writing Skill In English Study Program Universitas Muhammadiyah Of Bengkulu - Uswatun Hasanah; Waslurachim Safitri (Teaching English and Language Learning English Journal, 2024)
This study was to investigate students' perceptions of ChatGPT on writing skill in English Study Program of Muhammadiyah University. The purpose of this study was to find out the perceptions of students of English education program in ChatGPT for writing skill. This research is a qualitative descriptive method. In this study, researchers used questionnaires and interviews in obtaining data. The subjects of this study were fourth semester and sixth semester students who attended writing classes. The result of this study shows that the use of ChatGPT in the fourth and sixth semester of Language Education Study Program has been utilized well. As a result, the researcher was able to make a strong classification of the data collected, suggesting that students see the use of ChatGPT as an aid in the process of improving writing skills although there are still students who do not give a positive response to ChatGPT but overall the results of the research and discussion show that students give a good response to ChatGPT during the learning process. They showed positive responses to the ease of use of ChatGPT, increased knowledge, satisfaction with the speed and accuracy of ChatGPT responses, more efficient use of time, and increased engagement. Keywords: Writing Skill, ChatGPT, Perception,Student